Analysis of the Application of Banking Principles Related to Loss of Priority Customer Funds (Case Study of PT. Bank Rakyat Indonesia Tbk Takengon Branch Office) - Shely Shely (Lafadz Jaya Publisher, 2023)
The basic foundations in the world of banking have a great influence on the economy in Indonesia so that it will have an impact on banking activities. In essence, the function of banking is to unite public funds consisting of savings and redistribute public funds in the form of credit so as to improve the community's economic order as explained in Law Number 10 of 1998 concerning Banking. There are four types of banking principles, namely the fiduciary relations principle, the prudential principle, the secrecy principle, and the know-how customer principle. These four banking principles will be closely related to the cases that have been passed by PT. Bank Rakyat Indonesia Takengon Branch in relation to the case of missing priority customer funds. This article aims to know, understand, and analyze banking laws, especially the application of the principles related to the loss of priority customer funds. The research method uses normative legal research as it is based on laws and conceptual legal research. The results of research from this legal science journal are that there are actions that are not in accordance with applicable legal provisions and this case is directed at PT. Bank Rakyat Indonesia Takengon branch that does not heed or apply banking principles regarding the loss of priority customer funds. Thus, the analysis of cases of loss of priority customer funds is not only reviewed in terms of banking principles, but also the accountability of the bank. The research method uses normative legal research as it is based on laws and conceptual legal research. The results of research from this legal science journal are that there are actions that are not in accordance with applicable legal provisions and this case is directed at PT. Bank Rakyat Indonesia Takengon branch that does not heed or apply banking principles regarding the loss of priority customer funds. Thus, the analysis of cases of loss of priority customer funds is not only reviewed in terms of banking principles, but also the accountability of the bank. The research method uses normative legal research as it is based on laws and conceptual legal research. The results of research from this legal science journal are that there are actions that are not in accordance with applicable legal provisions and this case is directed at PT. Bank Rakyat Indonesia Takengon branch that does not heed or apply banking principles regarding the loss of priority customer funds. Thus, the analysis of cases of loss of priority customer funds is not only reviewed in terms of banking principles, but also the accountability of the bank. The results of research from this legal science journal are that there are actions that are not in accordance with applicable legal provisions and this case is directed at PT. Bank Rakyat Indonesia Takengon branch that does not heed or apply banking principles regarding the loss of priority customer funds. Thus, the analysis of cases of loss of priority customer funds is not only reviewed in terms of banking principles, but also the accountability of the bank. The results of research from this legal science journal are that there are actions that are not in accordance with applicable legal provisions and this case is directed at PT. Bank Rakyat Indonesia Takengon branch that does not heed or apply banking principles regarding the loss of priority customer funds. Thus, the analysis of cases of loss of priority customer funds is not only reviewed in terms of banking principles, but also the accountability of the bank.